2018
DOI: 10.1111/1467-8454.12130
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Power of us Monetary Policy Uncertainty Shock on Stock Returns in Australia and New Zealand

Abstract: This paper utilises time‐varying causal tests to re‐examine the international spillovers from US monetary policy uncertainty (MPU) shock on stock returns in Australia (AUR) and New Zealand (NZR). Interestingly, we find that, during the Dot‐com bubble from 1997 to 2001, the MPU would positively cause AUR. The reason behind is that increasing MPUs due to the speculations on Dot‐com firms provide favourable opportunities to investors. In contrast, we find negative prediction from MPU to AUR for a few months after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…As a result, future T&lSR are likely to be lower after periods of higher domestic and European economic policy uncertainty. This finding is consistent with Cai (2018), who pointed out that US monetary policy uncertainty negatively predicted Australian stock returns for a few months after the European debt crisis. However, as the forecast horizon extended to one year (12 months), the predictive power of the independent variables turns out to be irrelevant.…”
Section: Resultssupporting
confidence: 92%
“…As a result, future T&lSR are likely to be lower after periods of higher domestic and European economic policy uncertainty. This finding is consistent with Cai (2018), who pointed out that US monetary policy uncertainty negatively predicted Australian stock returns for a few months after the European debt crisis. However, as the forecast horizon extended to one year (12 months), the predictive power of the independent variables turns out to be irrelevant.…”
Section: Resultssupporting
confidence: 92%
“…They do this for everyday issues of the Washington Post, the Wall Street Journal and the New York Times. This index has been used as a proxy for MPU by Cai (2018) Under this basis, there are two MPU indices for USA constructed by Baker et al (2016). One is built using hundreds of daily newspapers covered by Access World News, and the other is based on ten major newspapers, such as USA Today, the Miami Herald, the Chicago Tribune, the Washington Post, the Los Angeles Times, the Boston Globe, the San Francisco Chronicle, the Dallas Morning News, the Houston Chronicle and the Wall Street Journal.…”
Section: Methodsmentioning
confidence: 99%
“…Although extensive literature has analysed the impact of EPU on stock markets, few studies have specifically related MPU to stock markets. Studies such as the one by Bernanke and Kuttner (2005) have shown that unforeseen changes by the Fed in the general fund rate are responsible for a small part of the general variability of stock prices, showing that a hypothetical unanticipated 25-basis-point cut in the rate would be related to a 1% increase in stock indices (Cai, 2018). This approach is supported by Sinha (2016), who argues that a greater uncertainty regarding interest rates has significant implications for economic agents' decision-making, acting as a negative shock in the demand.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Recently, it has been found that the spillover effect of MPU has the nonlinear time-varying feature. For instance, Cai (2018) pointed out the nonlinear spillover effect of US MPU on return on stocks in Australia and New Zealand.…”
Section: Literature Reviewmentioning
confidence: 99%